Case report: Reproductive organ preservation and subsequent pregnancy for an infertility patient with lynch syndrome-associated synchronous endometrial cancer and colon cancer after treatment with a PD-1 checkpoint inhibitor - Cao, Di; Gao, Yu; Zhang, Rong-xin; Wang, Fu-long; Li, Cong; Wu, Miao-qing; Liu, Yi-fan; Li, Dan-dan; Chen, Gong (Frontiers in Immunology, 2022)
Currently, immune checkpoint inhibitors (ICIs) are the mainstay of treatment for Lynch syndrome patients. However, the tumor regression features in radiology and pathology are inconsistent for patients who are treated with ICIs, which sometimes confuses surgical decision-making. Here, we report a case in which a 36-year-old patient suffering from infertility was diagnosed with Lynch syndrome-associated synchronous endometrial cancer and colon cancer, and persistently enlarged left iliac paravascular lymph nodes were detected after receiving sintilimab treatment, a programmed cell death 1 (PD-1) receptor inhibitor. Fortunately, when she was about to undergo hysterectomy and bilateral salpingo-oophorectomy, intraoperative pathology examination did not reveal any cancer cells in these lymph nodes, and therefore, her reproductive organs were preserved. Later, the patient successfully conceived and gave birth to a healthy male neonate with no immune-related adverse events (irAEs) during an 11-month follow-up. This case indicates that surgeons should carefully inspect the imaging characteristics after immunotherapy and that organ preservation is possible even for patients who fail to achieve complete clinical regression, which is especially important for female patients of childbearing age.